Evaluation of the relationship between quality of vision and visual function in Japanese glaucoma patients - Hideko Sawada (Dove Medical Press, 2011)
Hideko Sawada, Takeo Fukuchi, Haruki AbeDepartment of Ophthalmology, Niigata University Medical and Dental Hospital, Niigata, JapanPurpose: To evaluate the correlation between quality of vision (QOV) and visual function in glaucoma patients.Patients and methods: The relationship between QOV and visual function was investigated in 200 Japanese glaucoma patients. QOV was assessed using the Japanese version of the 25-item National Eye Institute Visual Function Questionnaire. The better eye and the worse eye were defined based on the mean deviation (MD) value of the Humphrey Field Analyzer program 30-2. A single linear regression analysis was applied to assess the relationship.Results: The lowest subscale score was observed in general health followed by general vision and driving. Visual acuity and the central 10° MD value in the better eye and the central 30° MD value in the worse eye were highly correlated with QOV. Threshold MD values at which patients began to have lower QOV ranged from —2 to —12 dB in the better eye and from —7 to —16 dB in the worse eye.Conclusion: Loss of visual function in both the better and the worse eye is significantly correlated to QOV. QOV of glaucoma patients begins to decrease in the early stages of visual field defects.Keywords: glaucoma, 25-item National Eye Institute Visual Function Questionnaire, visual field, visual acuity, quality of vision